A study to evaluate the prognostic significance of thrombocytopenia among critically ill children - Mundkur, Suneel C.; Upadhyay, Ranjani; Hebbar, Shrikiran A.; Kini, Pushpa; Bhaskarananda, Nalini; Shashidhara, Sowmya (International Journal of Contemporary Pediatrics, 2019)
Background: Pediatric critical care differs from Adult critical care not only in age but also in the outcomes. There are no studies regarding thrombocytopenia in the pediatric population. Therefore, in the current study, our objective was to study the prevalence and, the severity of thrombocytopenia, clinical features, and prognostic significance of low platelet count as an independent predictor of mortality and prolonged hospital and ICU stay. Methods: This was a prospective observational study conducted at tertiary care paediatric intensive care unit in India. Children between 1 month to 18 years admitted to the Pediatrics intensive care unit with thrombocytopenia due to any cause at admission were involved in the study. Detailed history was documented. Haemoglobin levels, total leucocyte counts, platelet counts, and platelet indices were recorded on the first and fourth day of admission. Outcomes were analysed in term of survivors and non-survivors and duration of ICU and hospital stay. Results: The study group consisted of 150 children with mean age of 8.458(± 5.604) years. Majority of children in the study group had severe thrombocytopenia 77 (51.3%). Moderate and mild thrombocytopenia was seen in 35(23.3%) and 38(25.4%) children respectively. Infection (50.66%) was the most common cause of thrombocytopenia, followed by sepsis (10.66%). Sepsis (27.5%) was observed to be the most common cause of mortality. Rise in platelet count on the fourth day among survivors, and no survivors were observed in 79.1% and 15.9% respectively. Failure of the rise in platelet count on the fourth day of admission was significantly associated with mortality (p value=0.001). The severity of thrombocytopenia does not correlate with duration of hospital and ICU stay. Conclusions: Platelet counts and indices at the time of admission to a critical care unit have limited use as a prognostic marker for predicting mortality in children.